The educational experiences of children in England during the Second World War - Lautman, Emma (2016)
This study explores the education of children living on the home front in England, and to a lesser extent Wales, during the Second World War. It uses oral histories, written memories and contemporary material, such as classroom work and children’s diaries, alongside archival documents. This multi-faceted approach allows us to ask what young people thought about school and in what ways their lives in the classroom adhered to or differed from the plans of political and educational authorities. In doing so, this thesis contributes to a growing literature which sets out to incorporate the child’s perspective into histories of education.